Analisis Perencanaan Produksi Gamis dengan Menggunakan Metode Agregat di Marwah Fashion Tasikmalaya - Ernawati; Ajeng Sabarini Muslimah; Seli Orintianti (LPPM Sekolah Tinggi Teknologi Cipasung, 2022)
Marwah Fashion is a company engaged in the convection sector that produces robes, tops, and veils of various types. The problem at Marwah Fashion at this time is that it cannot predict production for the next period, due to the uncertain number of requests from consumers. If these problems continue to occur, then Marwah Fashion will suffer losses because it cannot meet consumer demand optimally. In this study, problem-solving was carried out using the heuristic aggregate method by performing 3 methods, namely the calculation of labor control, subcontracting, and hybrid overtime and inventory. From the calculation results, the method that produces the minimum total cost is Hybrid Overtime and Inventory, which is Rp. 24.059.000,-.